Effect of Mefenamic Acid to Acupuncture Therapy on Carrageenan-Induced Inflammatory Pain in the Hind Limb of Rat - Yovita Mercya; Andreanus A Soemardji; Felesia Fanty (Journal of Medicine and Health, 2017)
Nonsteroidal anti-inflammatory drug (NSAID) and acupuncture are treatments forinflammatory pain. The purpose of this study is to see the effectiveness of mefenamic acid, adrug from the class of NSAIDs compared with acupuncture therapy in 24 male Wistar rats thathave received intraplantar induced of carrageenan. The experimental animals are divided intosix groups: pain control group, mefenamic acid group, before-induction acupuncture group,after-induction acupuncture group, before-induction mefenamic acid-acupuncture combinationgroup, and after-induction mefenamic acid-acupuncture combination. Inflammation and painassessment with inflammation volume and pain threshold parameters tenderness is done every60 minutes during 6 hours after induction of carrageenan. The results of animal studies showthat the combination of mefenamic acid - acupuncture before induction (inflammation inhibitionvalue of 40.24%; pain inhibition value 8.95%) shows a significantly smaller value (p <0.05) inreducing inflammation and increasing the pain threshold compared to single mefenamic acidgroup (inflammation inhibition value 58.53%; the pain inhibition value 29.09%) and singleacupuncture therapy before induction (inflammation inhibition value 78.04%; the paininhibition value 23.07%). It happens because mefenamic acid inhibits the action of acupunctureas an analgesic. This study concludes that the administration of mefenamic acid degrades theeffectiveness of acupuncture therapy in addressing inflammatory pain.Keywords: acupuncture, mefenamic acid, carragenaan, analgesic, antiinflammation